Comparative Evaluation of Hemato-biochemical and Oxidative Parameters of Racing Horses - Atata, Jamila Abdulhamid; Ajadi, Abdullateef Abiodun; Adam, Muhammed; Olatunji, Aishat Omobolanle; Bisalla, Muhammed; Adamu, Sani (Media Kedokteran Hewan, 2025)
Racing horses are prone to alterations in hemato-biochemical and oxidative stress parameters. The aim of this study was to determine the effect of racing on hemato-biochemical, and oxidative stress parameters of racing horses. Blood samples were collected from 15 control and 15 racing horses at four intervals (before, immediately after, 30 minutes after, and 24 hours after) to assay for hematological, serum biochemical, and oxidative stress markers.  The result revealed significant changes (P < 0.05) in vital parameters such as erythrocyte count, hematocrit index, hemoglobin concentration, leucocyte count, lymphocyte, neutrophil, neutrophil: lymphocyte ratio, total protein, albumin, urea, creatinine, cortisol, lactate, lactate dehydrogenase, creatinine kinase, aspartate aminotransferase, while glucose, cholesterol, triglyceride, gamma-glutamyl transferase, malondialdehyde, glutathione peroxidase, and catalase remained unaltered (P > 0.05). The alteration in hemato-biochemical parameters reported in this study only lasted for about 30 minutes after racing, with all values returning to the baseline range by 24 hours post-race. Interestingly, the comparable activities of antioxidant stress markers reported suggests that the horses have developed adaptive mechanisms that have conferred them with increased resistance to oxidative stress and reduced oxidative damage. This study demonstrates the importance of schematic monitoring of racing horses peri-racing to prevent racing-induced pathophysiological alterations and promote their general wellbeing.